Media literacy and media appropriations by youth - Reia-Baptista, Vítor (2013)
Nowadays everyone would agree to the growing, urgent need to enhance the understanding and the capacity of process analysis within Media Literacy and Media Education, given the increasing influence of the new media upon life styles and behaviours of all citizens, but especially the younger ones. Indeed, the twin issues of awareness-raising and developing processes to improve media literacy present all Member-States of the European Union, as well as the rest of Europe and the world, with a major challenge. Somehow, it is less important to recognize the problem of media literacy than to discuss how to foster the development and use of educational tools that would help the young generations, today and in the near future, to better develop a critical and informed attitude regarding the media.